Inside the blackbox of firm environmental efforts: Evidence from emissions reduction initiatives - Catrina Achilles; Peter Limbach; Michael Wolff; Aaron Yoon (University of Cologne, Centre for Financial Research (CFR), 2024)
Using project-level data from the Carbon Disclosure Project, we demonstrate how firms actually reduce greenhouse gas emissions. Most firms mainly pursue projects with small investments (median 127,000) and short payback periods (maximum three years). Firms experiencing shortterm performance pressure, smaller in size, and with shorter decarbonization horizons are more likely to implement such projects. Short-term projects focus on energy efficiency (e.g., LED upgrades) rather than involving transformative technology. They yield more expected annual carbon dioxide (CO2) and monetary savings and have greater NPVs than the average longer-term project, but exhibit lower total CO2 savings over the projects' lifetime. Firms with a greater share of short-term projects exhibit higher future environmental ratings, but it is a combination of shortand long-term projects that generates the most expected CO2 savings. Our evidence suggests that typical firm climate engagements are neither costly nor long-term oriented. In sum, firms tend to mitigate rather than adapt to climate change.
Keywords: D25; D62; G30; M41; Q54; 330; Climate change; Corporate greenhouse gas emissions reduction initiatives; Environmental investment decisions; ESG ratings; Financial incentives; Investment horizon